2012
DOI: 10.1111/j.1469-8986.2012.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient fear conditioning and self‐reported psychopathy: The role of fearless dominance

Abstract: The role of the two dimensions of psychopathy -dispositional fearlessness (theorized to reflect variations in reactivity of the brain's defensive system) and externalizing proneness (presumed to reflect variations in function of anterior regulatory systems)-in fear learning was examined in a sample of undergraduates assessed using the Psychopathic Personality Inventory-Revised (PPI-R) who participated in a differential aversive conditioning task. Only scores on selfreported 'fearless dominance' -irrespective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 82 publications
3
87
4
2
Order By: Relevance
“…Surprisingly, a few correlations were found between FD scores and higher levels of initial pain catastrophizing and fear-related variables, along with higher subjective painfulness. These results are inconsistent with the wellestablished notion of a lack of fear in FD (Fowles & Dindo, 2009;Hale, Goldstein, Abramowitz, Calamari, & Kosson, 2004;López, Poy, Patrick, & Moltó, 2013). It is possible that these results stem from the limited number of participants.…”
Section: Discussioncontrasting
confidence: 79%
“…Surprisingly, a few correlations were found between FD scores and higher levels of initial pain catastrophizing and fear-related variables, along with higher subjective painfulness. These results are inconsistent with the wellestablished notion of a lack of fear in FD (Fowles & Dindo, 2009;Hale, Goldstein, Abramowitz, Calamari, & Kosson, 2004;López, Poy, Patrick, & Moltó, 2013). It is possible that these results stem from the limited number of participants.…”
Section: Discussioncontrasting
confidence: 79%
“…Related to the Emotionality factor, Fearfulness, Anxiety, and Dependence facets were negatively correlated to the DAPTQ, but not sentimentality. Multiple studies identified a link between PPI-I and resilience to fear and anxiety, alongside low emotional reactivity (López, Poy, Patrick, & Moltó, 2013;Uzieblo et al, 2010). Considering the strong association between PPI-I and the DAPTQ, these results support the capacity of the DAPTQ to assess adaptive traits closely related to the psychopathic personality (Durand, in press).…”
Section: Discussionsupporting
confidence: 57%
“…The dualor two-process conceptualization posits that separate neural mechanisms differentially contribute to the affective-interpersonal and impulsive-antisocial components of psychopathy, namely, trait fearlessness, which reflects a deficit or under-reactivity of s aversive/defensive motivational system, and externalizing vulnerability, which reflects impairments in the frontocortical systems that mediate anticipation, planning, and inhibitory control (for empirical evidence, see, for example, Carlson, Thái, & McLarnon, 2009;Heritage & Benning, 2013;López, Poy, Patrick, & Moltó, 2013;Patrick, Durbin, & Moser, 2012;Patrick & Lang, 1999;Venables, Hall, Yancey, & Patrick, 2015). Consistent with this perspective, studies examining the differential contribution of psychopathy components to reduced startle potentiation have demonstrated that this deficit is specifically related to the interpersonal and affective features of psychopathy, but not to its externalizing features.…”
Section: Introductionmentioning
confidence: 99%